2022
DOI: 10.4049/jimmunol.2001141
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Calcium Signal Induces NK Cell Degranulation but Inhibits Its Cytotoxic Activity

Abstract: The raw files presented in this article have been submitted to the Gene Expression Omnibus (https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi) under accession number GSE184127.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It is possible that a similar behavior could be observed in ex vivo expanded NK cells, wherein NK cells with the highest proliferative potential and a less mature phenotype will have better persistence and overall efficacy in vivo. The current study did not address the relationship between degranulation and cytotoxicity, which could be complex; for instance, it was shown that enhanced calcium signaling induces NK cell degranulation but inhibits cytotoxicity (Li et al, 2022). NK cells may also exhibit a fast granzyme‐mediated killing and switch to a slow death receptor‐mediated killing during subsequent tumor cell encounters (Prager et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that a similar behavior could be observed in ex vivo expanded NK cells, wherein NK cells with the highest proliferative potential and a less mature phenotype will have better persistence and overall efficacy in vivo. The current study did not address the relationship between degranulation and cytotoxicity, which could be complex; for instance, it was shown that enhanced calcium signaling induces NK cell degranulation but inhibits cytotoxicity (Li et al, 2022). NK cells may also exhibit a fast granzyme‐mediated killing and switch to a slow death receptor‐mediated killing during subsequent tumor cell encounters (Prager et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…To test the ability of PD-L1-pHLIP in combination with avelumab to trigger NK cytotoxicity, two scenarios, namely plate-coated and mircobeads-coupled, were exploited. In addition, CD107a (a biomarker of NK degranulation following cytotoxicity was induced) and IFN-γ (a major proinflammatory mediator released by activated NK cells) as key parameters of antigen/mAb-triggered ADCC function [ [20] , [21] , [22] ], were detected in our system. As a result, plate-coated immobile PD-L1-pHLIP plus avelumab actively stimulated significantly increased expression of CD107a as well as IFN-γ in NK cells compared with control protein plus avelumab or PD-L1-pHLIP plus IgG1 isotype, in a dose-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study has provided evidence that the inhibition of NK cell clustering could downregulate the IFN-γ secretion ability of NK cells [38]. Furthermore, the defects in 2B4 (CD244)/CD48 led to a decrease in intracellular calcium release, which could impede perforin assembly and the exocytosis of soluble granules [35,39,40]. As such, IFN-γ is a representative indicator to evaluate the activation and priming of NK cells.…”
Section: Discussionmentioning
confidence: 99%